Performance evaluation of environmentally benign nonionic biosurfactant for enhanced oil recovery. (15th December 2018) - Seo, Seokju; Mastiani, Mohammad; Mosavati, Babak; Peters, Derek Michael; Mandin, Philippe; Kim, Myeongsub
Highlights: Biosurfactant derived from tannic acid is effective to reduce interfacial tension (IFT) of crude oils. The degree of IFT reduction by the biosurfactant is greater than that with a conventional chemical. Biosurfactant flooding provides better sweeping efficiency than sodium dodecyl sulfate (SDS) flooding. Droplet-based microfluidics provides a simple and cost-effective test platform for IFT measurements. Abstract: Chemical enhanced oil recovery (EOR) is a successful method for increasing crude oil recovery. However, chemicals commonly used for enhanced oil recovery operations possess adverse biological impacts. To meet the legislative requirement and environmental protection demands, the performance of a highly biodegradable nonionic surfactant derived from tannic acid, a possible alternative, was evaluated using a microfluidic technology for the replacement of chemically synthesis surfactant by green chemistry products. Aqueous microdroplets containing the surfactant in crude oils were used for measurements of interfacial tension (IFT) reduction. The degree of interfacial tension reduction by sodium dodecyl sulfate (SDS), one of the most popular conventional surfactants, was also quantified for performance comparison. The potential of the biosurfactant for IFT reduction of light crude oil was superior to that of SDS. To evaluate the feasibility of the biosurfactant in improvement of recovery efficiency, surfactant-assisted flooding was tested under a random microfluidic network at the optimal concentrations, and the results were in good agreement with IFT reduction tests. The utilization of the polymer in a biosurfactant synthesis process effectively enhanced high sweep efficiency by decreasing a viscous fingering effect. The biosurfactant proved to be adequate and can sufficiently alleviate environmental concerns adopted by chemical flooding EOR.